Using MCDA to select refurbishment solutions to improve buildings IEQ - Silva, Sandra Monteiro (2013)
Due to buildings high energy consumption their refurbishment is essential to achieve the targets defined by the EPBD-recast regarding energy efficiency and reduction of carbon emissions. Besides the energy efficiency, the sustainability and the Indoor Environmental Quality (IEQ) of Buildings must also be considered when planning a refurbishment project. Thus, to propose an effective building refurbishment it is necessary to select the adequate construction solutions taking into account their impact on the energy performance, thermal and acoustic comfort, indoor air quality and environmental impact of the building. In this work a multi-criteria decision analysis method is applied to balance all these aspects in a refurbishment project, in order to assist the design team on the selection of the construction solutions. Throughout the multi-criteria analysis performed, it was possible to verify that the rehabilitation solutions with lower embodied energy were the best refurbishment options.